If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9l + -22 = 23 + 4l Reorder the terms: -22 + 9l = 23 + 4l Solving -22 + 9l = 23 + 4l Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-4l' to each side of the equation. -22 + 9l + -4l = 23 + 4l + -4l Combine like terms: 9l + -4l = 5l -22 + 5l = 23 + 4l + -4l Combine like terms: 4l + -4l = 0 -22 + 5l = 23 + 0 -22 + 5l = 23 Add '22' to each side of the equation. -22 + 22 + 5l = 23 + 22 Combine like terms: -22 + 22 = 0 0 + 5l = 23 + 22 5l = 23 + 22 Combine like terms: 23 + 22 = 45 5l = 45 Divide each side by '5'. l = 9 Simplifying l = 9
| X=-8+15 | | 4m+6=17 | | 13w+39= | | y-2=.666x-27 | | 3.3x-4.2=-0.4 | | y-(-5)=-11 | | 11y-7.5-7y=2 | | C=3.50p+550 | | 48+12s= | | 8(e+6)=3(e+33) | | -34+x+36=32 | | (2x+5)=(3x-8) | | 4(2b+-6)+11=8b+-13 | | 1.5y-7=0.5y | | 5+x+x=2x+6 | | y-7=-.5x-(-6) | | 4a+10=8a+2 | | 11x-(6x-5)=110 | | 3x-4y+5z=-1 | | (2x+10)=(7y-8) | | 2x+-8y=-4 | | 4a-10=8a+2 | | -(-2)+10(-6)= | | 10-6x=4+46 | | 10n-10=4+12(n+11) | | -2(-8q+7)+5q= | | 21=4X-9X | | 3x^4+31x^3+56x^2=0 | | -b+3b-2=2-4b+12 | | 5(5x+1)+4=26x+2 | | (2x+5)=(7x-15) | | 38=p-12 |